Apocrypha from the History of the Jewish Military Union and its Authors - Libionka, Dariusz (Zagłada Żydów. Studia i Materiały, 2008)
This article is an attempt at a critical analysis of the history of the Jewish Fighting Union (JFU) and a presentation of their authors based on documents kept in the archives of the Institute of National Remembrance in Warsaw. The author believes that an uncritical approach and such a treatment of these materials, which were generated under the communist regime and used for political purposes resulted in a perverted and lasting picture of the history of this fighting organisation of Zionists-revisionists both in Poland and Israel. The author has focused on a deconsturction of the most important and best known “testimonies regarding the Warsaw Ghetto Uprising”, the development and JFU participation in this struggle, given by Henryk Iwaƒski, WΠadysΠaw Zajdler, Tadeusz Bednarczyk and Janusz Ketling–Szemley.A comparative analysis of these materials, supplemented by important details of their war-time and postwar biographies, leaves no doubt as to the fact that they should not be analysed in terms of their historical credibility and leads one to conclude that a profound revision of research approach to JFU history is necessary.